2014
DOI: 10.1002/cncy.21476
|View full text |Cite
|
Sign up to set email alerts
|

Multiplatform comparison of molecular oncology tests performed on cytology specimens and formalin‐fixed, paraffin‐embedded tissue

Abstract: BACKGROUND: Molecular oncology testing is important for patient management, and requests for the molecular analysis of cytology specimens are increasingly being made. Formalin-fixed, paraffin-embedded (FFPE) cell blocks of such specimens have been routinely used for molecular diagnosis. However, the inability to assess cellularity before cell block preparation is a pitfall of their use. In this study, various cytologic preparations were tested with several molecular test platforms, and the results were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 17 publications
2
78
0
Order By: Relevance
“…Given the diversity of cytopathologic specimen types and the different methods of fixation and processing available, options for procuring DNA from cytologic specimens for molecular analysis vary; material can be successfully obtained from cell blocks, smears, cytospins, and liquid-based preparations. 7,9,11,12,14,[19][20][21][22][23][24][25] Most commonly, cell blocks are used for molecular testing on cytopathologic specimens. 21 The cell block closely approximates surgical pathology material; tissue fragments from cytopathologic specimens are embedded in paraffin and are sectioned akin to surgical specimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the diversity of cytopathologic specimen types and the different methods of fixation and processing available, options for procuring DNA from cytologic specimens for molecular analysis vary; material can be successfully obtained from cell blocks, smears, cytospins, and liquid-based preparations. 7,9,11,12,14,[19][20][21][22][23][24][25] Most commonly, cell blocks are used for molecular testing on cytopathologic specimens. 21 The cell block closely approximates surgical pathology material; tissue fragments from cytopathologic specimens are embedded in paraffin and are sectioned akin to surgical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The successful use of smeared slides to acquire DNA for EGFR testing has been described in several publications. 9,11,28 Smears are decoverslipped, and tumor cells are removed from areas of the slide with a high tumor fraction by scraping with a scalpel or dissecting needle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytological materials that were obtained with easily reproducible and comfortable methods constitute a valuable resource for diagnosis and treatment studies in routine pathological process. Studies have shown that cytological specimens used in molecular studies show up to 100% compatibility with histological specimens (12). Especially in the majority of non-small cell lung carcinomas, the diagnosis is provided with cytological material and small biopsies.…”
Section: Key To Success In Molecular Processes: Communicationmentioning
confidence: 99%
“…According to statistics, the diagnosis and molecular profiling of 25%-30% NSCLCs are made by small biopsies, and up to 40% by cytology biopsies [15]. The success rates of both small and cytology biopsies range between 83% and 100% in published studies [16][17][18][19][20][21]. It is known that 90% of patients with early stage NSCLCs who receive surgical resections or have locally advanced NSCLCs and receive definitive chemoradiation, eventually relapse [22].…”
Section: Introductionmentioning
confidence: 99%